Host‐plants of leaf‐miners in Australian subtropical rainforest - Maunsall, S; Burwell, C; Morris, R; McDonald, W; Edwards, E; Oberprieler, R; Kitching, R (Wiley, 2016)
Leaf‐miners are endophytic insect herbivores that are considered to be relatively host‐specific compared with other types of insect herbivores, often depending on one or a few congeneric hosts. Because of their degree of host‐specificity, they may be particularly vulnerable to environmental change. Despite this, little is known about the host‐plants and life histories of the Australian leaf‐mining fauna. Here we present new information on the host‐plant use of leaf‐miners occurring in Australian subtropical rainforest. We repeatedly hand‐collected leaf‐miners at 14 sampling sites in the ‘Tweed Caldera’ subtropical rainforest region of south‐eastern Queensland and north‐eastern New South Wales, Australia. Leaf‐miners and their host‐plants were identified to species (or morphospecies in the case of some leaf‐miners). Within the region, a total of 106 plant species was recorded as leaf‐miner hosts, on which a total of 12 679 individual leaf‐miners was counted, belonging to 50 different species. We measured the local host‐plant range of each leaf‐miner species for which we had reliable incidence records across sampling sites (24 species). Local host‐specificity was relatively high with 66.7 % of species recorded from a single or two congeneric host‐plants. 16.7 % of species were restricted to a single plant family and 16.7 % were recorded on a few to several plants of the same plant order or across a range of unrelated host‐plants.